Family Support as a Mediator between Perceived Organizational Support and Work Engagement among Female Workers - Ima Mawarti; Maharani Tyas Budi Hapsari (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2026)
A The aim of this study is to determine the effect of family support as a mediating variable in the relationship between perceived organizational support and work engagement among female workers in the textile industry. The research hypothesis states that perceived organizational support has a significant effect on work engagement with family support as a mediating variable. This study uses a quantitative approach with regression analysis and mediation testing using Hayes’ Process Model 4. Perceived organizational support was measured using the scale developed by Rhoades & Eisenberger (2002), which includes the dimensions of fairness, supervisor support, and organizational rewards and job conditions. Family support was measured using Friedman’s (2013) scale, which covers emotional, instrumental, informational, and appraisal support. Work engagement was measured using the Utrecht Work Engagement Scale (2004), which consists of the dimensions vigor, dedication, and absorption. The results of the study show that perceived organizational support has a significant effect on work engagement both directly and indirectly through family support as a mediator. This indicates that family support significantly mediates the relationship between perceived organizational support and work engagement among female workers. This indicates that organizations need to strengthen perceived organizational support through women-friendly policies that promote balance between work and family roles. For female workers, it is important to build cooperative family relationships so that family support becomes more effective and positively contributes to their work engagement.